FROM PAROCHIALISM TO UNIVERSALISM - Zaini Othman; Md Saffie Abdul Rahim; Eko Prayitno Joko (Journal of Social Political Sciences, 2022)
In the context of the study of Sabah's political development, the contribution of Semporna and its community cannot be denied or dismissed. In fact, it is not an exaggeration to stated that Semporna has an interesting scientific dimension to be used as a corpus of knowledge in analyzing and digesting the political development of Sabah in general and Semporna in particular. Semporna in the geo-social context of Sabah is very synonymous with the Bajau community, the majority ethnic group that inhabits the area (Semporna). In the demographic context of Sabah, the Bajau community in Semporna is authoritatively known as "East Coast Bajau or Bajau Semporna". Based on field data collected semi-longitudinally (2018-2022), this article aims to analyze the political behavior of the Bajau Semporna community in a "parochial" cultural-political framework. Is the political culture still strong among the Bajau Semporna community? Is "parochial" political culture being the main basis in the process of making political decisions among Bajau-Semporna? To what extent does the modernization process affect or contest (contest) the "parochial" political culture? Based on the finding and data discussion, it is crystal clear that the premise underlies in this study suggest that modernization and socioeconomic development bring changes in values, norms and consciousness from parochialism to universal consciousness as per suggested by Robertson (1992), Giddens (1990) and Ohmae (1996).